Analysis of The Interaction Between Ecological Footprint, Green Technology And Financial Development in Türkiye: Evidence From Fourier Ardl Approach (Third Sector Social Economic Review, 2025)
Since the 1990s, the importance of concepts such as green technology, financial development and ecological footprint has increased in the economic literature; this situation has revealed the necessity of efforts to ensure environmental sustainability. This study uses the Fourier ARDL approach to investigate the relationships between ecological footprint (EFP), green technologies (GRE) and financial development (FIN) in Turkey in the period 1992-2021. The causality relationship between the variables was examined with traditional and Fourier causality tests. In addition, FMOLS, DOLS and CCR coefficient analyses were applied in order to see the long-term effects of independent variables. In addition to the results showing the existence of a long-term relationship, a one-way causality relationship from financial development to ecological footprint and from ecological footprint to green technologies was reached. The coefficient test results show that green technologies have a positive effect on reducing the ecological footprint; while financial development increases the ecological footprint. In light of the findings of the study, it is concluded that investments in green technologies should be increased in order for Turkey to achieve its sustainable economic growth targets. It is important that the steps to be taken to reduce the ecological footprint are not limited to technological innovations; the financial system should also be structured in a way that encourages environmentally friendly investments.
Keywords: Ecological Footprint; Green Technologies; Financial Development; Türkiye; Fourier ARDL